PECULIARITIES OF USING MARKETING COMMUNICATIONS IN THE FIELD OF TOURISM - Подзігун, Світлана; Малярчук, Наталія (Modern engineering and innovative technologies, 2023)
It has been proven that in today’s realities, tourism can be restored only under the conditions of the introduction of innovative technologies. In order to work at full capacity, Ukrainian travel agencies are looking for innovative ways of development an